MENUMBUHKAN KEPERCAYAAN DIRI DAN KREATIVITAS SISWA DALAM PEMBELAJARAN MAJAS MELALUI PENDEKATAN KOLABORATIF DI KELAS VI SD MUHAMMADIYAH 1 BONTANG - Salam Salam; Daroe Iswatiningsih; Lirra Zanni (J-SES : Journal of Science, Education and Studies, 2026)
Indonesian language learning in elementary schools plays a crucial role in developing students' language skills, critical thinking, and creativity. However, figurative language often presents difficulties due to its abstract nature, resulting in low self-confidence and limited creativity. This study aims to describe the application of a collaborative approach to fostering student self-confidence and to explain its role in enhancing the creativity of sixth-grade students at Muhammadiyah 1 Elementary School in Bontang. The research method used a qualitative descriptive approach with 28 students, an Indonesian language teacher, and the principal as subjects. Data were collected through observation, interviews, and documentation, then analyzed using the Miles & Huberman model and tested for validity through triangulation. The results showed that the collaborative approach effectively fostered student self-confidence, as evidenced by increased confidence in speaking, answering questions, and presenting in class. Furthermore, student creativity also increased, demonstrated by their ability to construct varied, meaningful, and contextually relevant figurative sentences. These findings align with previous theories and research that emphasize the role of collaboration in enhancing social skills, self-confidence, and creativity. In conclusion, the collaborative approach is relevant for implementation as an innovative strategy for Indonesian language learning in elementary schools. Keywords: self-confidence, creativity, figurative language, collaborative approach, elementary school